A Shock Mitigation of Pedestrian-Vehicle Impact Using Active Hood Lift System: Deploying Time Investigation - Tae-Hoon Lee; Gun-Ha Yoon; Seung-Bok Choi (Shock and Vibration)
This paper investigates the deploying time (or response time) of an active hood lift system (AHLS) of a passenger vehicle activated by gunpowder actuator. In this work, this is accomplished by changing principal design parameters of the latch part mechanism of the hood system. After briefly introducing the working principle of the AHLS operated by the gunpowder actuator, the governing equations of the AHLS are formulated for each different deploying motion. Subsequently, using the governing equations, the response time for deploying the hold lift system is determined by changing several geometric distances such as the distance from the rotational center of the pop-up guide to the point of the latch in the axial and vertical directions. Then, a comparison is made of the total response time to completely deploy the hood lift system with the existing conventional AHLS and proposed AHLS. In addition, the workable driving speed of the proposed AHLS is compared with the conventional one by changing the powder volume of the actuator.